Abordagem terapêutica miofuncional em casos de desvios fonológico, fonético e fonético-fonológico - Costa, Patricia Pereira (2011)
The theme of this work is the application of myofunctional therapy in cases of phonetic, phonological and phonetic-phonological disorders. The central hypothesis of this study is that the adequacy of the stomatognathic system structures involved in the articulation of linguistic segments favor the adequacy of speech in cases of phonological, phonetic and phonetic-phonological disorders. Thus, this research aimed to determine the effects of the myofunctional therapy in cases of phonological, phonetic and phonetic-phonological, disorders. For this research, we selected subjects who were waiting in the queue service, of Service Speech Pathology, Federal University of Santa Maria, to provide speech and Orofacial the period March 2010 to August 2010. Inclusion criteria of this study were the presence of phonological, phonetic and phonetic-phonological, and sthomatognatic system disorders. It was considered as exclusion criteria the presence of malformations, genetic syndromes, suspected neurological disorders, cognitive or psychological disorders, hearing difficulties, diagnosis of language delay, speech therapy before, and malocclusion. To select the sample were performed the following procedures: medical history, assessment of the stomatognathic system, articulatory examination, otorrinological examination and hearing screening. Of 22 patients evaluated, six were in accordance with the selection criteria, two with phonological disorder, two with phonetic disorder, and two with phonetic-phonological disorder. With age between 6 and 13 years old. After the evaluations were carried out two therapys weekly, the exercises were for myofunctional adequacy of stomatognathic sistem alterations. Surveys every eight sessions of evaluating the evolution of the subjects on the stomatognathic system and speech. Based on the results of descriptive analysis was performed. After the myofunctional therapy, subjects who had phonological disorder and phonetic disorder had proper speech. One of the subjects who had phonetic-phonological disorder was not entirely proper speech. Regarding sound classes benefited, myofunctional after therapy, the appropriateness of the stomatognathic system, the liquid sounds were acquired, and fricative sounds were partially stabilized. It was concluded that the myofunctional therapy was efficient in cases of phonological, phonetic and phonetic-phonological disorders in the presence of sthomatic system disorders.